2021
DOI: 10.1111/csp2.527
|View full text |Cite
|
Sign up to set email alerts
|

Rare coral and reef fish species status, possible extinctions, and associated environmental perceptions in Mauritius

Abstract: Mauritius is reported to have the highest marine species endemism in the Western Indian Ocean faunal Province but the status of these species has not been evaluated. To address this knowledge gap, 119 reef sites were sampled to evaluate populations of 16 species of rare and endemic reef fish and corals using scuba-based surveys conducted by citizen scientists and marine science professionals. Additionally, we interviewed $1,000 households in 27 coastal villages to determine their perceptions of the environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Fortunately, many of these species have broad semi-overlapping Indo-Pacific distributions that include places where the impacts are likely to be less severe. Many of the smaller range species lie at the outer limits of the Amphiprion/Premnas distribution, where the level of threat is likely to vary from species to species (McClanahan et al 2021). Our understanding of anemonefish biodiversity is likely a work in progress, with two new species recently recognized for the Pacific (A. barberi, and A. pacificus, Allen et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, many of these species have broad semi-overlapping Indo-Pacific distributions that include places where the impacts are likely to be less severe. Many of the smaller range species lie at the outer limits of the Amphiprion/Premnas distribution, where the level of threat is likely to vary from species to species (McClanahan et al 2021). Our understanding of anemonefish biodiversity is likely a work in progress, with two new species recently recognized for the Pacific (A. barberi, and A. pacificus, Allen et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that for marine fishes, small-range endemics tend to have higher population densities than their widespread counterparts at the same locations (Hobbs et al 2010(Hobbs et al , 2011. This has not been evaluated for anemonefishes, although McClanahan et al (2021) showed that the endemic A. chrysogaster at Mauritius is moderately abundant, is broadly distributed around the island, and has a large depth range. A complete understanding of extinction risks for island endemics will require a greater effort in estimating population densities and total population size.…”
Section: Rarity Traits: Double and Triple Jeopardymentioning
confidence: 99%
“…Thermal stress affecting corals have been observed by Mattan-Moorgawa et al ( 2012 ), Louis et al ( 2016 ) and McClanahan and Muthiga ( 2021 ). Environmental stressors may also be the reason for extinction of some endemic fish species (McClanahan et al 2021 ). Intuitively, one would expect a higher depletion for the groups of fishers who mainly target the reef species.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, lethal coral bleaching has been increasing in frequency, severity, and geographic scope over the past decades, and thus it is anticipated that this trend will continue (Grottoli et al 2014;Hughes et al 2017) which therefore increases the fragility of reefs (Goldberg and Wilkinson 2004) leading to biodiversity loss (McClanahan et al 2021) and rapid community structural changes (Tebbett et al 2023). To date studies on corals of Mauritius have looked at bleaching and mortality of corals under thermal stress (Bhagooli and Taleb-Hossenkhan 2012;Bhagooli and Sheppard 2012;Bhagooli and Kaullysing 2019;Bhagooli et al 2021b,c;Fai et al 2023;Jeetun et al 2023;Ricot et al 2023).…”
Section: Introductionmentioning
confidence: 99%